Ageism in Hiring: The Influence of Implicit Cues on Perceptions of Candidate Warmth, Competence, Suitability, and Trainability - Greene, Morgan A (East Carolina University)
This study investigates how implicit age cues in resumes and perceived technology ability influence hiring evaluations. Drawing from the Stereotype Content Model (Fiske et al., 2002), we examine how these cues affect perceptions of warmth and competence, which in turn shape judgments of trainability and suitability. In an experimental design with 588 participants, resumes were manipulated to include subtle age indicators and technology skill levels. Results showed that perceived technology ability significantly predicted warmth in some models, though this effect was not consistently observed across all analyses. Implicit age cues and their interaction did not significantly predict warmth or competence. Warmth did not significantly predict trainability or suitability, nor did it mediate the effects of age-related cues on outcomes. Competence significantly predicted both trainability and suitability, reinforcing its primacy in task-oriented evaluations. This supports prior findings that competence stereotypes play a central role in age-based hiring decisions (Cuddy et al., 2008; Hashim & Wok, 2013). Additionally, raters’ ageist beliefs predicted lower suitability and competence ratings, but higher trainability, suggesting complex prescriptive biases in candidate evaluations (North & Fiske, 2013b). These findings underscore how subtle cues and evaluator biases shape early hiring judgments and highlight the need for more structured, bias-reducing hiring practices (Derous & Decoster, 2017; Green et al., 2020).
Keywords: Psychology, Quantitative